Population structure, gene flow and relatedness of Natterer's bats in Northern England - Mordue, Simone; Aegerter, James; Mill, Aileen; Dawson, Deborah A.; Crepaldi, Carolina [UNESP]; Wolff, Kirsten (Springer, 2021)
There have been significant declines in population numbers of many bat species in the United Kingdom, including Natterer's bats Myotis nattereri, over the last century, largely due to anthropogenic changes. The philopatry, which temperate-zone bats often exhibit to their natal landscapes, in combination with anthropogenic threats, can lead to fragmentation, isolation and sub-division of populations. This may result in bottlenecks and declines in genetic diversity. Multi-scaled research is required to disentangle how the variation in the physical traits of bat species (e.g. affecting flight), as well as their social and behavioural traits (e.g. community size, migration, breeding systems), may affect the genetic health of populations and provide a potential buffer against fragmentation. We used microsatellite markers to characterise the genetic diversity and population structure present in Natterer's bat colonies to determine whether summer roosting bat colonies were spatially differentiated or part of a meta-population. Analyses of population structure and measures of genetic relatedness suggest spatially differentiated populations of bats exhibit long term site fidelity to summer roosting sites, whilst high genetic diversity at sites indicates gene exchange occurs via swarming sites. Natterer's bats in northern England may travel greater distances to swarming sites than has been previously documented.
Keywords: Genetic structure; Myotis; Natterer’ s bat; Population ecology